KONTRIBUSI TINGGI BADAN, KEKUATAN OTOT LENGAN DAN KELENTUKAN PERGELANGAN TANGAN TERHADAP KEMAMPUAN TEMBAKAN BEBAS PADA SISWA PUTERA KELAS XI - M Imran Hasanuddin (STKIP Paris Barantai, 2023)
The aims of the research was to determine the contribution of height, arm muscle strength and wrist flexibility to free shooting ability in male students of class XI SMA Negeri 13 Makassar. The method used in this research is descriptive quantitative approach and data collection is done through tests and measurements. The population in this study were all male students of SMA Negeri 13 Makassar and the samples taken in this study were 32 students using random sampling technique. The results of the analysis stated that there was a contribution of height (X1) to free throw ability (Y) of 21.5%, there was a contribution of arm muscle strength (X2) to free throw ability (Y) of 21.4%, there was a contribution of wrist flexibility (X3) to free throw ability (Y) of 20.3%, there is a contribution of height (X1), arm muscle strength (X2), and wrist flexibility (X3) to free throw ability (Y) of 48.5%. Keywords: Body height, arm muscle strength, wrist flexibility in basketball free shots.